ANALYSIS OF RESERVE POWER SUPPLY SYSTEMS OF RAILWAY AUTOMATION DEVICES - Bekh, Ya. P. (Systems and Technologies, 2023)
the use of signaling, centralization and blocking systems (SCB) makes it possible to increase the throughput and carrying capacity of railways, ensuring safe and uninterrupted movement of trains, and reduces the turnaround time of cars, increasing the speed of passenger and freight deliveries. Automation and telemechanics devices currently used in railway transport, according to the tasks they solve and areas of application, are divided into stage and station ones. Semi-automatic blocking regulates the movement of trains in areas with light traffic. Automatic blocking regulates the movement of trains using track traffic lights installed on the stretch, which divide the stretch into block sections. The indications of passing traffic lights change automatically under the influence of moving trains. The main element of the battery is track circuits, the main purpose of which is to determine the location of trains. Automatic locomotive signaling increases train safety and improves working conditions for locomotive crews. With their help, the readings of track traffic lights are transmitted directly to the driver’s cabin. Automatic crossing signaling and automatic barriers ensure the safety of train traffic when crossing railways at the same level as roads. These devices automatically activate traffic signal devices for vehicles and close the barrier when a train approaches and open it after the train has passed. Station systems regulate the movement of trains in stations and large areas: – electrical centralization of switches and signals – a set of automation and telemechanics devices that provide control of switches and signals of the entire station from one point by the station duty officer; – dispatch centralization is the most advanced and effective means of regulating train movement on railways. This system combines automatic blocking devices, electrical centralization and coded telecontrol and telesignaling systems. It allows you to control switches and signals from one point and makes it possible to concentrate all administrative and executive functions for regulating train traffic at the train dispatcher; – automation of sorting humps – a set of devices that increases the processing capacity of sorting humps. Therefore, ensuring their reliable operation, even in emergency situations, is an important task, and the use of alternative solutions provides economic and technical reserves.